2009
DOI: 10.1186/1477-7525-7-63
|View full text |Cite
|
Sign up to set email alerts
|

Measuring patient's expectation and the perception of quality in LASIK services

Abstract: BackgroundLASIK is the use of excimer lasers to treat therapeutic and refractive visual disorders, ranging from superficial scars to nearsightedness (myopia), and from astigmatism to farsightedness (hyperopia). The purposes of this study are to checking the applicability and psychometric properties of the SERVQUAL on Lasik surgery population. Second, use SEM methods to investigate the loyalty, perceptions and expectations relationship on LASIK surgery.MethodsThe method with which this study was conducted was q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 29 publications
5
24
2
Order By: Relevance
“…Generally, the patients have high expectations in private hospitals (4.91 of 5 [≈98%]), which is not unusual and similar to the results of previous studies accomplished in Cyprus [7], Turkey [4] and Taiwan [22,23]. The service quality of private hospitals have been satisfactory from the patients' perspective (4.02 of 5 [≈80%]), although there is much work to do for improvement in all areas of service quality.…”
Section: Discussionsupporting
confidence: 86%
“…Generally, the patients have high expectations in private hospitals (4.91 of 5 [≈98%]), which is not unusual and similar to the results of previous studies accomplished in Cyprus [7], Turkey [4] and Taiwan [22,23]. The service quality of private hospitals have been satisfactory from the patients' perspective (4.02 of 5 [≈80%]), although there is much work to do for improvement in all areas of service quality.…”
Section: Discussionsupporting
confidence: 86%
“…The 2006 research was in agreement with the research of Lim and Tang, 2000 which stated that responsiveness had the largest service quality gap (Lim & Tang, 2000). The 2011 research is in agreement with the results from other researchers who state that the largest service quality gap was in the empathy dimension (Lam, 1997;Lin et al, 2009). The results from all the research in the General Hospital of Katerini showed a particularly high gap between expectations and perceptions.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies related to service quality in healthcare systems have used a modified SERVQUAL scale to measure healthcare service quality and patient satisfaction in hospitals, clinics or medical centre environments (Babakus & Mangold, 1992;Headley & Miller, 1993;Youssef, Nel, & Bovaird, 1995;Lam, 1997;Lim & Tang, 2000;Wisniewski & Wisniewski, 2005;Lin et al, 2009). All the previous research has proved that all dimensions have gaps between expectations and performance.…”
Section: Tangiblesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the competition for quality rehabilitation services has been increasing, as a key element of the healthcare system (9)(10)(11).Overall, the quality of medical services reflects two components: technical and functional. Sincethe evaluation of the technical component (diagnostic and therapeutic processes) is difficult for patients, they are more likely to assess the functional services (services processes) (12).…”
Section: Introductionmentioning
confidence: 99%